2016
DOI: 10.1016/j.neulet.2016.06.050
|View full text |Cite
|
Sign up to set email alerts
|

REST levels affect the functional expression of voltage dependent calcium channels and the migratory activity in immortalized GnRH neurons

Abstract: REST levels affect the functional expression of voltage dependent calcium channels and the migratory activity in immortalized GnRH neurons, Neuroscience Letters http://dx.doi.org/10. 1016/j.neulet.2016.06.050 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Various Ca 2+ signaling was repressed by REST differentially [106]. The functional expression of P/Q-type channels was increased by REST silencing in GN11 neuron cells [107], while the promotor activity of N-type Ca 2+ channel alpha 1B was not influenced by REST in NS20Y cells [108]. Recently, REST was found to control spatial K buffering in primary cortical astrocytes, impairing neuronal activity [109].…”
Section: Neuronal Transmission and Synaptic Plasticitymentioning
confidence: 99%
“…Various Ca 2+ signaling was repressed by REST differentially [106]. The functional expression of P/Q-type channels was increased by REST silencing in GN11 neuron cells [107], while the promotor activity of N-type Ca 2+ channel alpha 1B was not influenced by REST in NS20Y cells [108]. Recently, REST was found to control spatial K buffering in primary cortical astrocytes, impairing neuronal activity [109].…”
Section: Neuronal Transmission and Synaptic Plasticitymentioning
confidence: 99%
“…Indeed, consistent with their trajectories, the microtubuleassociated protein stathmin (Stmn2) and the repressor element-1 silencing transcription factor (Rest) promote migration in immortalized GnRH neurons. 24,41 The trajectory analysis of GnRH-negative cells revealed T-box transcription factor 3 (Tbx3) as a gene with high expression in the early stages in the nasal compartment (Fig. 3f).…”
Section: Spatiotemporal Expression Trajectories Define Gnrh Neuron De...mentioning
confidence: 99%
“…Indeed, a recent study has shown REST co-expressed in GnRH neurons, which increases the functional expression of calcium channels and reduces their migratory potential (Antoniotti et al, 2016). The chemical nature of REST-positive neurons in the pre-optic and midbrain areas needs to be identified.…”
Section: Expression Of Rest In Glial Cells and Neuronsmentioning
confidence: 99%